The Playful Strategies and Their Contribution to Generation of New Knowledge in University Students - Martha Patricia Cuadro Solórzano, María Rodríguez Gámez (International Journal of Advanced Science and Technology, 2020)
The objective of the research is to carry out a characterization of the playful strategies that can be used to generate new knowledge in university students. The Desk Research methodology was used, under which a review was carried out on studies referring to the aspects that can promote the generation of knowledge, as well as the identification of characteristics present in play strategies, which can facilitate the development of capacities. cognitive and thought styles in university students. It was obtained as a result that the application of playful strategies is adequate for developing research skills and abilities in university students, due to the training generated in the repetition of activities related to their future professional practice, in a motivating environment and low stress.